Characteristics of new particle formation events occurred over the Yellow Sea in Springtime from 2019 to 2022 - Ahn, Chanwoo; Yum, Seong Soo; Park, Minsu; Seo, Pyosuk; Yoo, Hee-Jung; Lee, Meehye; Lee, Hyunmin (Elsevier BV, 2024)
Characteristics of atmospheric new particle formation (NPF) events were investigated using the data obtained from the ship measurement campaign named Yellow Sea Air Quality (YES-AQ) over the Yellow Sea during the springtime from 2019 to 2022. NPF events occurred 15 times for the valid 128 observation days for the four-year period, and the average and standard deviation formation rate (FR) and growth rate (GR) of the NPF events were 2.38 +/- 1.53 cm(-3) s(-1) and 4.11 +/- 2.81 nm h(-1), respectively. The FR and GR were close to those in urban regions, implying the unique characteristics of the Yellow Sea. Owing to the NPF events, the number concentrations of total aerosols and nucleation mode particles increased by approximately 7850 and 6002 cm(-3), respectively, and those of cloud condensation nuclei at 0.2% and 0.6% supersaturation increased by about 1269 and 3269 cm(-3), respectively. The NPF events mostly occurred under the meteorological conditions of low temperature and relative humidity as well as high solar radiation and wind speed. These meteorological conditions appeared predominantly when the air mass originated from the continent north of the Korean Peninsula. The current analyses based on the data measured repeatedly during a specific period each year, which were not well conducted in other maritime NPF studies, highlight the reliability of the presented characteristics of NPF events over the Yellow Sea.